HOW LIFE TRANSITION HAS AFFECTED THE CONSUMER BEHAVIOUR OF CHINESE INTERNATIONAL STUDENTS IN THE UK: AN GENERAL PERSPECTIVE - Feng, Ruilan (2008)
There is increasing number of Chinese students study abroad in the UK during recent years. Most of these students are in their late adolescence or emerging adulthood. They are in the life transition from adolescence to adulthood as well as in the transition to be international students in the UK.